Implementasi Latihan Batuk Efektif Dalam Upaya Pembersihan Jalan Nafas Pada Pasien Pasca Anestesi Umum Di Ruang Pemulihan - Rachmasari, Astry; Suryani, Roro Lintang; Nur Adriyani, Fauziah Hanum (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Common side effects of general anesthesia, particularly when administered by inhalation, include sore throat, coughing, and hoarseness after surgery. An effective cough is an attempt to alleviate sore throat, cough, and hoarseness in individuals who have had general anesthesia. In order to keep the lungs clean, it is important to cough properly so that secretions may be removed swiftly and efficiently. Objective: At Jatiwinangun Surgical Specialty Hospital, we aim to teach our patients how to cough effectively so that they can reopen their airways following general anesthesia. Method: After one round of general anesthesia, 30 participants will undergo effective coughing activities as part of this activity's methodology. One technique to evaluate a cougher's ability to clear their airways is with the use of a checklist and an observation sheet for airway clearing. This method takes into account the cougher's breathing rate, the noises they make when coughing, the strength of their breathing muscles, and how easily they clear their airways. Result: Ten participants (or 33.3% of the total) fell within the 26–35 age bracket, while nineteen (or 63.3% of the total) were female, fourteen (or 46.7% of the total) had only completed high school, and ten (or 33.3% of the total) were housewives. At least 21 participants (70.0%) had more knowledge regarding how to effectively apply cough training after receiving good-quality education, whereas 6 participants (20.0%) had adequate knowledge and 3 participants (10.0%) had less. After undergoing general anesthesia, 24 subjects (80.0%) had effective coughing abilities, whereas 6 people (20%) shown less competence. When it came time to observe airway clearance, the results showed that 93.3% of participants breathed normally, 83.3% did not make any extra ronchi breath sounds, 90.0% did not use any additional breathing muscles, and 80.0% of participants had no trouble clearing their airways. Conclusion: From the results of PkM it can be concluded that effective cough training can clear the airway in patients after general anesthesia.